Optimasi Beban Mengajar Dosen Teknik Informatika Menggunakan Algoritme Genetika - Femilia Nopianti; Agus Wahyu Widodo; Muh. Arif Rahman (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Determining lecturers' burden of teaching is a routine activity in all universities, especially for department administrator in each faculty. This matter done as the number of classes taken by students in each semester is always different, yet the number of lecturers are relatively fixed. Determining lecturers' burden of teaching must be done so that the lecturer does not exceed the maximum limit and the teaching process will not deviate from lecturer's interest. The Informatics Engineering program of the Faculty of Computer Science, Brawijaya University Malang is still carrying out the process of determining lecturers' burden of teaching manually, so that it requires a lot of time because it has to adjust between the interest of the subject with lecturer's interest. One optimization method that can be used to overcome this problem is a genetic algorithm. The genetic algorithm process in this study uses integer number representation, crossover method with one cut point crossover, mutation method with reciprocal exchange mutation and random mutation, and selection method with elitism selection. Based on the tests performed, optimal parameters were obtained, the number of population was 70, the combination of cr and mr respectively 0.5, and the number of generations was 4000 with the highest fitness value produced was 0.090909.